O clima urbano das cidades do interior do estado de São Paulo: uma análise do campo térmico de Assis, Cândido Mota, Maracaí e Tarumã - Ortiz Porangaba, Gislene Figueiredo [UNESP] (2015)
Since the Industrial Revolution, changes in land surface were intensified by the rapid growth of cities and the urban environmental problems have increased, affecting the city dweleers' quality of life. So, some events began to occur more frequently, as the increase of rainfalls, the increase of air pollution, the fall of relative humidity and the increase of the air temperature, generating a new local climate - the urban climate. In this sense, this research has as the central objective analyzing the urban climate of the cities of Assis, Cândido Mota, Maracaí and Tarumã, from the viewpoint of the thermal field, primarily responsible for the production of the cities climate characteristics. Among these, the first is configured as a medium-sized city and the others are small cities located in the west region of the São Paulo state. Thus, the hypothesis of this research is that the cities studied, even being medium and small, have already showed modifications in the thermal and hygrometric field, since it already have changes in its surface by urbanization. The research method to be used will be the Urban Climate System proposed by Monteiro (1976), considering the thermodynamic subsystem based on the human perception of thermal comfort canal. They classified geoecological and geourban attributes of the cities studied. Later, gathering meteorological data was made through fixed and mobile points simultaneously in all the cities proposals, to see how each one of them affects the temperature and humidity in the performance of these weather systems. The data collected enabled the elaboration of letters of isotherms and isoígras to, thereby, trace the urban atmosphere of the cities under the acting of the upper atmospheric systems